Pemanfaatan Rimpang Lengkuas Merah (Alpinia Purpurata K.Schum) sebagai Fungisida Tanaman Selada yang Menopang Inovasi Green Chemistry - Wulan Ayu Ningsih; Intan Farhani; Kailla Qothrunnada Qurrota’ayun; Syifa Aulia Rahmawati; Iqbal Mustapha (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Indonesia is a country rich in useful biodiversity, such as red galangal (Alpinia purpurata K.Schum). The antibacterial and antifungal activity of the compounds isolated from the red galangal rhizome is the beginning of a new innovation to implement the concept on plants. The content of 1,8 sineol and eugenol in it makes red galangal rhizome can be used as a fungicide on lettuce plants. The widespread use of chemical-based pesticides can harm farmers and the environment with repeated exposure and over a long period of time. So biofungicide innovation is needed that can support the concept of Green Chemistry. The purpose of this study is to determine the effectiveness of red galangal rhizome extract as a fungicide on lettuce plants, as well as to analyze and determine under what conditions the fungicide from red galangal rhizome extract is optimal in eradicating Rhizoctonia Solani fungus on lettuce plants. This research was conducted experimentally using a completely randomized design (CRD) with 10 treatments. All data were tested for normality followed by homogeneity test and all data were found to be normally distributed and homogeneous. Data were analyzed with parametric statistical tests using one-way ANOVA tests and further tests using Tukey with an error rate of 10% to determine whether there was an effect of the treatment tested on the material. The results of this study indicate that red galangal rhizome extract is effective in eradicating Rhizoctonia Solani fungus on lettuce plants with an optimum concentration of 50%.